MeDASH: An Effective Way to Check the Availability of Pharmaceutical Drugs in Proximity Using QR-codes - Kommey, Benjamin; Klogo, Griffith Selorm; Paha, Linda Ama; Yeboah, Ofosu Samuel; Ofori , Asamoah Davies (Universitas Ahmad Dahlan, 2024)
Background: The rapid advancement of technology is reshaping industries, including healthcare. Doctors and pharmacists require efficient tools to manage inventory and meet patient needs effectively.. Contribution: This project introduces a mobile application that leverages QR code technology to provide real-time information on the availability of prescribed drugs in nearby pharmacies. Method: The app has two interfaces. The doctor’s interface records prescription details (drug name, dosage, frequency) and generates a QR code for the patient. The patient’s interface scans the QR code to find nearby pharmacies with the prescribed drugs via a central database. Results: The application generates QR codes within 0.19 seconds and displays them in 0.22 seconds on average. It integrates Google Maps to identify the patient’s location and nearby pharmacies, offering precise directions to the selected pharmacy. Conclusion: This solution enhances healthcare delivery by improving access to prescription drugs, offering convenience for both healthcare providers and patients, and addressing drug availability challenges.